2021
DOI: 10.3390/ma14123326
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachta indica Leaf Extract as Green Corrosion Inhibitor for Reinforced Concrete Structures: Corrosion Effectiveness against Commercial Corrosion Inhibitors and Concrete Integrity

Abstract: The construction industry has extensively demanded novel green inhibition strategies for the conservation and protection of carbon steel-reinforced concrete structures. For the first time, the effect of Azadirachta indica leaf extract (Neem) as a potential corrosion inhibitor of carbon steel in reinforced concrete under corrosion in saline simulated media was evaluated. To assess the corrosion inhibition behavior of the Neem natural organic extract, three inorganic commercial inhibitors were tested to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…An extensive analysis on the safety of the already-mentioned green corrosion inhibitors will be of paramount importance in the future, to avoid unforeseen deleterious effects for the human safety. The effects on the mechanical properties of only a few green corrosion inhibitors has been evaluated up to this date, providing satisfactory results comparable with nitrite compounds [28,44,46,51]. However, the vast majority of the green inhibitors mentioned in this review still need further studies on the topic, and this will play a key role in the selection process of a valid alternative to nitrites.…”
Section: Discussion and Comparison With Nitritesmentioning
confidence: 94%
See 1 more Smart Citation
“…An extensive analysis on the safety of the already-mentioned green corrosion inhibitors will be of paramount importance in the future, to avoid unforeseen deleterious effects for the human safety. The effects on the mechanical properties of only a few green corrosion inhibitors has been evaluated up to this date, providing satisfactory results comparable with nitrite compounds [28,44,46,51]. However, the vast majority of the green inhibitors mentioned in this review still need further studies on the topic, and this will play a key role in the selection process of a valid alternative to nitrites.…”
Section: Discussion and Comparison With Nitritesmentioning
confidence: 94%
“…In particular, 1.4% of guar gum extract vs. cement weight can impart an IE% of 71.1%, in the presence of 3.5% NaCl vs. cement weight, thanks to the inhibition of the anodic reaction kinetics. Azadirachta indica (neem) leaf extract [51] is used for corrosion inhibition tests performed in concrete samples exposed to a 3.5 wt.% NaCl solution for 128 days. In contrast to other studies, the authors investigate the inhibitive effect of the molecule in delaying chloride ion penetration.…”
Section: Tests In Concretementioning
confidence: 99%
“…Also, Bambusa arundinacea extract prevents the conversion of hydroxide from calcium to calcite and has a pore-blocking effect [214]. Valdez-Salas et al [215] investigated the effect of Azadirachta indica leaf extract on the corrosion inhibition of steel in concrete mortars contaminated by aggressive chloride. The results showed that Azadirachta indica does not change the integrity and physicochemical parameters of concrete, and after 182 days of investigation, it showed a long-term protection against corrosion of 95%, which is a similar result to commercial inhibitors.…”
Section: Using Plants As Gcismentioning
confidence: 99%
“…They use ethanol to extract the inhibitor from the bark roots of Nauclea latifolia to protect mild steel from the H 2 SO 4 solution. Another concern is the achievement work [17] to recognize that roots and seeds extract of Azadirachta indica was utilized to characterize the corrosion protection under the same solution. Weight loss and gasometric techniques are sufficient to support the Freundlich adsorption isotherm result to conserve corrosion damage.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%